2002
DOI: 10.1192/bjp.181.43.s3
|View full text |Cite
|
Sign up to set email alerts
|

First-episode schizophrenia, bipolar disorder and other psychoses in a rural Irish catchment area: Incidence and gender in the Cavan–Monaghan study at 5 years

Abstract: BackgroundThe potential of first-episode studies in schizophrenia is maximised through systematic epidemiological, clinical and biological comparisons between homogeneous populations of the psychoses.AimsTo conduct prolonged accrual of ‘all’ cases of non-affective and affective psychotic illness on an epidemiologically complete basis.MethodWithin the region covered by Cavan–Monaghan psychiatric service (population 102 810), all putative cases of first-episode psychosis were diagnosed using DSM–IV.ResultsFrom 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
5
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 41 publications
8
27
5
2
Order By: Relevance
“…Studies have shown that paranoia is associated with immigration and low socio-economic status (Kendler, 1982), refugee status (Westermeyer, 1989), victimisation and stressful life events (Johns et al, 2004). There is also some evidence associating madness in clinical populations and paranoia in the general population (Johns et al, 2004) to maleness: in their study controlling for the confounding effects of urbanicity and migration, Scully et al (2002) found that paranoid and other core schizophrenia diagnoses were 7.5 times more likely to be given to men than women.…”
Section: Societal Feeling and Paranoiamentioning
confidence: 98%
“…Studies have shown that paranoia is associated with immigration and low socio-economic status (Kendler, 1982), refugee status (Westermeyer, 1989), victimisation and stressful life events (Johns et al, 2004). There is also some evidence associating madness in clinical populations and paranoia in the general population (Johns et al, 2004) to maleness: in their study controlling for the confounding effects of urbanicity and migration, Scully et al (2002) found that paranoid and other core schizophrenia diagnoses were 7.5 times more likely to be given to men than women.…”
Section: Societal Feeling and Paranoiamentioning
confidence: 98%
“…Qualitative research has itself been implicated in (colonial) oppression (Denzin & Lincoln 2000), and quantitative research can be politically progressive, for example, in demonstrating the classed, gendered, racialised character of schizophrenia diagnoses (Boydell et al 2001;Harrison et al 2001;Scully et al 2002). Nevertheless, critics have shown that quantitative psychological methods have many negative political connotations.…”
mentioning
confidence: 99%
“…Other studies have shown that paranoia is associated with immigration and low socio-economic status (Kendler, 1982), refugee status (Westermeyer, 1989), victimisation and stressful life events (Johns et al, 2004). There is also evidence that paranoia is associated with maleness, both in the general population (Johns et al, 2004) and in clinical samples, where for example paranoid and other core schizophrenia diagnoses are 7.5 times more likely to be applied to men than women (Scully et al, 2002) In contrast to psychiatry, in recent years British clinical (predominantly cognitive) psychologists have conducted innovative research focusing on particular kinds of homogeneous psychotic experience (unusual beliefs, hearing voices) rather than heterogeneous diagnostic categories (e.g. schizophrenia).…”
Section: Paranoia Psychiatry and Clinical Psychologymentioning
confidence: 97%